Tingkat kepuasan pemustaka terhadap program Inkubator Literasi Pustaka Nasional Perpusnas Press periode tahun 2022 - Ratmono, Damaji (Al-Kuttab : Jurnal Kajian Perpustakaan, Informasi dan Kearsipan, 2024)
ILPN is a local wisdom-based book acquisition program organized by Perpusnas Press Publishers. ILPN aims to encourage, develop and accelerate the ability and success of readers to produce written works. The problem in this research is how readers assess the ILPN activity process during the 2022 period, the materials/workshops provided in the ILPN program, the themes set by the 2022 ILPN program, and the timeline of ILPN activities. The aim of this research is to determine user satisfaction with the ILPN program. The method used to analyze this research data uses quantitative descriptive methods. The population in this research is library users who took part in the ILPN program in 2022. This research used a survey technique with questions on Google form and took 87% of the sample population, namely 131 respondents from 150 populations in 14 ILPN loci in 2022. Data processing techniques using data selection, data percentage, analyzing data using a measurement scale. The research results showed that the overall average score of the elements assessed was 4.42. The conclusion obtained is that library users who took part in ILPN in 2022 stated that they were very good/satisfied with the ILPN program in 2022